Teaching Dialogue and Polylogue to Non-Linguistic Students: Competence-Based Approach - I. E. Abramova; O. M. Sherekhova (Высшее образование в России)
Competence-based approach to the use of practice-oriented technologies and the creation of an innovative learning environment is the current trend of Russian higher education. The task of developing graduates’ communicative competence for the implementation of effective corporate communication and labor interaction in a multicultural business environment is still relevant. Being obligatory components of modern professional activity, dialogue and polylogue in English provide information exchange, promote joint decision-making, effective interaction and creative cooperation between specialists of different nationalities as well. Mastering the correct strategy in foreign language communication in the business world makes it possible to overcome language and communication barriers. It has a positive effect on building trust in multinational teams, on which the performance of the entire company depends. The authors analyze a number of difficulties associated with the teaching of these types of communication in the classroom. The article examines the foreign and domestic experience of teaching dialogue and polylogue and describes innovative methods of training students for professional communication. The authors of the article investigate the readiness of students for foreign language communication in professional discourse and describe the practical experience of teaching dialogue and polylogue to non-linguistic students using alternative methods simulating real communicative situations in business communication. It is concluded that the competence-based approach is effective in developing the communicative competence of non-linguistic students in the classroom bilingualism.